Vietnam and Siam: from Friendship to Confrontation (1802–1835) - Dinh Co Nguyen; Xuan Hiep Tran; Tuan Binh Nguyen (Przegląd Nauk Historycznych)
The article presents and explains the changing process of relations between Vietnam and Siam in the early 19th century during the rule of the first two kings of the Nguyen Dynasty, Gia Long and Minh Mang. Due to inherited factors from the past and internal problems, Vietnam and Siam always maintained friendly relations during the first two decades of the nineteenth century, even supporting each other against external threats. However, each side had its own goals and was taking steps to strengthen its position in the region. The malevolence in the relations between the Nguyen court and the Chakri dynasty began to grow gradually, culminating in the reigns of King Minh Mang (Vietnam) and King Rama III (Siam).